Data Expansion and Conceptual Structure. - Revsine, Lawrence (The Accounting Review, 1970)
The article examines the rationale of the proposed expansion of data used in external reporting. A new approach to external reporting has emerged in the recent accounting literature. Much of the accounting research over the past several decades has emphasized alteration or augmentation of reported data within the confines of the historical cost model. Financial decision-makers have access to a wide range of data. Government and business periodicals provide an abundance of information regarding macro-environmental events such as the state of the economy and factors relevant at an industry-wide level. Expanding the range of data provided is viewed as a means of overcoming the limitations of contemporary reports without necessitating detailed knowledge of user decision models. Social psychologists differentiate human information processing structures by their degree of concreteness. It was suggested above that the actual financial environment confronting the statement user is complex. Such inherent complexity necessitates simultaneous analysis of many variables in order to establish the expected future financial impact of a given series of observed events. This position is predicated on the assumption that detailed information about user decision models is needed to support the choice of a particular measurement model.